Electrochemical ELISA based on Escherichia coli with autodisplayed Z-domains - Lee, Ju-Kyung; Gu-Yoo; Park, Min; Jose, Joachim; Kang, Min-Jung; Pyun, Jae-Chul (ELSEVIER SCIENCE SA, 2012)
Recently, we reported autodisplayed Z-domains on Escherichia coli can highly improve the sensitivity of immunoassays through the orientation control of detection antibodies. In this work, the amperometric analysis was applied to the immunoassay based on E. coli cells with autodisplayed Z-domains. For amperometric analysis, the reduction current of 3,5,3',5'-tetramethylbenzidine (TMB) was measured at the potential of -50 mV and the correlation between the reduction current and the OD value was estimated to be 28 nA/OD and the limit of detection was calculated to be 0.07 in OD unit. In this work, the feasibility of the immunoassay based on amperometric analysis was presented by the quantification of HRP as a model analyte. For the demonstration of medical diagnosis, C-reactive protein (CRP) was detected by using electrochemical ELISA based on E. coli with autodisplayed Z-domains. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: C-REACTIVE PROTEIN; SPR BIOSENSOR; HORSERADISH-PEROXIDASE; OUTER-MEMBRANE; E. COLI; IMMUNOASSAY; LAYER; FILM